Committee Member of Persatuan Staf Akademik UMP PAKAD - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 30 August 2021 - Congratulations to all academicians from FK who are being appointed as committee member of Persatuan Staf Akademik UMP (PAKAD) for 2021-2023 session.